Επίδραση της μελατονίνης στην ανθεκτικότητα φυτών βασιλικού (Ocimum basilicum) στην αλατότητα - Παύλου, Γιαν-Ιουλιάν (Τμήμα Γεωπονικών Επιστημών, Βιοτεχνολογίας και Επιστήμης Τροφίμων, Σχολή Γεωτεχνικών Επιστημών και Διαχείρισης Περιβάλλοντος, Τεχνολογικό Πανεπιστήμιο Κύπρου, 2017)
Due to the decrease of crop yield caused by abiotic stress factors such as salinity and the increased future need for food, there is an ongoing research to develop a cost – efficient method to encounter the decreased crop production. A promising method is the usage of plant chemical priming. Melatonin is a tryptophan-based molecule that has been used with success for plant priming in many researches. The aim of the current experiment was to find if there are any effects of exogenous melatonin applied with the method of plant priming on basil plants which were exposed to high salinity stress and under control conditions. The results show enhancement of the salinity tolerance attributes of basil with the usage of 5μΜ melatonin concentration. The results direct towards the continuation of the experiments on the topic with the aim to conduct a field experiment, in order to evaluate the potential effect of melatonin as a plant priming agent under field conditions.
Keywords: Salinity; Plant priming; Melatonin; Basil; Χημική έναυση φυτού; Μελατονίνη; Αλατότητα; Βασιλικός